Clinical Characteristics and Outcomes of Pediatric Cerebral Venous Sinus Thrombosis: An Analysis of 30 Cases in China - Wang, Xin-Hua; Zhang, Lin-Mei; Chai, Yi-Ming; Wang, Ji; Yu, Li-Fei; Zhou, Shui-Zhen (Frontiers in Pediatrics, 2019)
Objective: To summarize the etiological, clinical and imaging characteristics of cerebral venous sinus thrombosis (CVST) in children so as to provide the basis for early diagnosis and prompt treatment. Methods: We retrospectively analyzed the data of 30 patients with a diagnosis of CVST admitted to Children’s Hospital of Fudan University from 2008 to 2018. All the medical records including clinical manifestations, laboratory data, neurological findings, treatment and short-term prognosis were analyzed. Results: (1) Regarding the etiology: Among the 30 cases, the causes of CVST were infection (7/30), tumor (3/30), nephritis or nephrotic syndrome (8/30), traumatic brain injury (1/30), and undefined disease (11/30). However, 11 out of all the 30 cases without definite cause were presented with subacute or chronic headache associated with progressive or acute exacerbation. (2) Diagnosis：All the 30 cases were definitely diagnosed as CVST after neuroimaging examination using brain magnetic resonance imaging (MRI) combined with magnetic angiography venography (MRV). (3) Short-term prognosis：all the patients were treated with anticoagulation and finally 26 cases improved. Conclusions: For cerebral venous sinus thrombosis patients, they usually do not have any specific clinical manifestations, which would lead to high rate of misdiagnosis and delayed therapy. Increased consideration and prompt MRV checkup play a key role in the accurate diagnosis. Anticoagulation is safe and effective for treatment.